Chemikalienfreie Bekämpfung von Holzschädlingen durch dielektrische Erwärmung mit Radiowellen und Mikrowellen. Issue 8 (27th June 2014) - Hoyer, Christian; Pfütze, Christian; Plarre, Rudy; Trommler, Ulf; Steinbach, Steffen; Klutzny, Kerstin; Holzer, Frank; Rabe, Carsten; Höhlig, Björn; Kopinke, Frank‐Dieter; Schmidt, Detlef; Roland, Ulf
<x xml:space="preserve">Abstract</x> Thermal pest control requires long treatment times due to the low thermal conductivity of wood and may lead to the formation of cracks. Here, the thermal treatment with radio waves as well as microwaves has been studied. The direct dielectric heating has the advantage of a good homogeneity. The obtained temperature profiles for radio waves were more homogeneous compared to microwaves. Detailed studies showed that elimination of pests was not related to the application of the electromagnetic field itself, but due to the temperature increase.